POLYMER ACTION ON CORROSION RATES OF STEEL IN CEMENT MORTAR - Ribeiro, M. S. (2014)
At the National Laboratory of Civil Engineering (LNEC), Portugal, and with financial support from Fundação para a Ciência e a Tecnologia (FCT) given to the research project PTDC/ECM/101810/2008 – Polymer-modified Cement Mortars for the Repair of Concrete Structures, an ongoing study aims to assess the possible prevention of steel corrosion induced by carbonation in PCMs and to set new research topics based on the results, due to the potential effect of polymers on the properties of cement mortar that have been shown to influence the corrosion of embedded steel, such as the reduction of water absorption and ionic mobility and the increase in electrical resistivity and resistance to CO2 uptake. The action of styrene-butadiene and acrylic-styrene polymers on steel corrosion in cement mortars was assessed after steel depassivation was induced by carbonation in an environment meeting the required conditions for progression of steel corrosion.